The high fidelity and unique error signature of human DNA polymerase ε - Korona, Dagmara A. (Oxford University Press, 2011)
Bulk replicative DNA synthesis in eukaryotes is highly accurate and efficient, primarily because of two DNA polymerases (Pols): Pols δ and ε. The high fidelity of these enzymes is due to their intrinsic base selectivity and proofreading exonuclease activity which, when coupled with post-replication mismatch repair, helps to maintain human mutation rates at less than one mutation per genome duplication. Conditions that reduce polymerase fidelity result in increased mutagenesis and can lead to cancer in mice. Whereas yeast Pol ε has been well characterized, human Pol ε remains poorly understood. Here, we present the first report on the fidelity of human Pol ε. We find that human Pol ε carries out DNA synthesis with high fidelity, even in the absence of its 3′→5′ exonucleolytic proofreading and is significantly more accurate than yeast Pol ε. Though its spectrum of errors is similar to that of yeast Pol ε, there are several notable exceptions. These include a preference of the human enzyme for T→A over A→T transversions. As compared with other replicative DNA polymerases, human Pol ε is particularly accurate when copying homonucleotide runs of 4–5 bases. The base pair substitution specificity and high fidelity for frameshift errors observed for human Pol ε are distinct from the errors made by human Pol δ.